НАБЛЮДЕНИЯ ИОНОСФЕРНЫХ ВОЗМУЩЕНИЙ ПО ДАННЫМ ПРОХОЖДЕНИЯ РАДИОВОЛН НА НАКЛОННЫХ ТРАССАХ - Кравец, Р. О. (Одеські астрономічні публікації, 2011)
We propose ionosphere disturbances registration method, which is based on the radio broadcasting signals observations. The essence of the method is that during the strong ionosphere disturbances, the radio stations signal power is greatly decreased. The advantage of the method, compare to other existing methods, is that it allow more quickly get information about ionosphere disturbances.